The Impact of Intangible Assets, Financial Performance and Stock Prices of Companies Listed on the Stock Exchange of Thailand - Hannimitkulchai, Kwanchanok; Watcharanukul, Krittapong; Aupathum, Naetiphum; Phannarangsi, Chakkaphong; Piwdet , Panupong; Lohaphong, Santisuk (KKBS Journal of Business Administration and Accountancy, 2025)
This study aims to examine the relationship between intangible assets and both return on equity (ROE) and stock prices, as well as the role of ROE as a mediating variable between intangible assets and stock prices of companies listed on the Stock Exchange of Thailand. The sample includes 472 companies, totaling 944 observations. Data analysis was conducted using descriptive statistics, Pearson’s correlation coefficient, and multiple regression analysis to test the hypotheses. The results reveal that intangible assets are positively related to both ROE and stock prices. Additionally, ROE shows a positive relationship with stock prices and serves as a partial mediator between intangible assets and stock prices. These findings provide valuable insights for corporate executives in evaluating the return on investment in intangible assets, formulating effective management strategies, and ensuring appropriate financial disclosures. This, in turn, can enhance investor confidence and strengthen the firm's sustainable competitive advantage.